Design and Integration Issues in Developing a Managed Learning Environment Which is Responsive to Changing Curriculum and Policy Requirements - Cotterill, Simon; Skelly, Gordon; McDonald, Tony (Proceedings of the International Conference on Networked Learning, 2004)
The virtual learning environment for undergraduate medicine at the University of Newcastle (‘the NLE’), was established by 1998 and currently supports over 1,400 students and over 1,600 contributing staff. The NLE and wider managed learning environment is continually developed and refined in response to changes in curriculum and policy requirements, including support for learning over a wide geographical area. The purpose of this paper is to report on the design and integration issues of the NLE with reference to these changes. We provide usage data and critically examine the implications of the integrated approach at Newcastle and relate this to student learning.